1984
DOI: 10.1203/00006450-198407000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Factors Controlling Aldosterone Secretion during Hypoxemia in Fetal Lambs

Abstract: SummaryFactors modulating the fetal aldosterone response to hypoxemia were studied in three groups of chronically catheterized fetal lambs between 131 and 143 days of gestation (term, 145 days). One group (control group) received an infusion of 5% dextrose in water; the second group (captopril-treated group) was given captopril, an inhibitor of angiotensin-converting enzyme; the third group (captopril plus dexamethasone-treated group) received dexamethasone in addition to captopril. In all groups of fetuses, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
3
0

Year Published

1985
1985
2008
2008

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…Although there was an association between fetal acidemia and high potassium levels in cord blood, there was no correlation between aldosterone and potassium levels, suggesting that umbilical cord aldosterone concentrations are not related to potassium levels. This finding confirms fetal lamb studies which showed that the rise in plasma aldosterone levels during hypoxemia is not related to activity of renin-angiotensin system or to high potassium levels (13).…”
supporting
confidence: 89%
“…Although there was an association between fetal acidemia and high potassium levels in cord blood, there was no correlation between aldosterone and potassium levels, suggesting that umbilical cord aldosterone concentrations are not related to potassium levels. This finding confirms fetal lamb studies which showed that the rise in plasma aldosterone levels during hypoxemia is not related to activity of renin-angiotensin system or to high potassium levels (13).…”
supporting
confidence: 89%
“…Relatively low 11β-HSD2 expression in the late gestation fetal lung would allow binding of circulating cortisol to MR in the fetal lung even in unstressed fetuses before term; free cortisol levels in the ovine fetus at 120–130 days of gestation are estimated to be 1–2 n M , within the range for binding at ovine or human MR (ovine MR: K i 0.2 n M , K d 0.5 n M [38]; human MR: K i 0.13 n M [39]). Moreover, fetal cortisol levels are approximately 20-fold higher than those of aldosterone in the unstressed fetus, suggesting that cortisol is likely to be the sole ligand at MR in 11β-HSD2 deficient tissues prior to term, except in conditions of fetal hypoxia in which aldosterone would be increased sufficiently to also bind appreciably at MR [40]. In guinea pig fetal lungs, treatment with aldosterone has been shown to significantly decrease the rate of lung fluid production [41], indicating a role of MR in reabsorption in that species.…”
Section: Discussionmentioning
confidence: 99%
“…The release of renin from the ovine kidney occurs even at this very young age (0.6 gestation) in response to hypotension caused by hemorrhage (9). Hypoxia is known to be only a weak-to-modest stimulus to renin and ANG II production in the fetus (8,17,25,31); however, there have been no studies of the effects of asphyxia on the fetal RAS. From this literature, we hypothesized that the development of hydrops fetalis after asphyxia in the 0.6 gestation sheep fetus would be associated with activation of the fetal RAS.…”
mentioning
confidence: 99%